Enhanced light trapping in dye-sensitized solar cell by coupling to 1D photonic crystal and accounting for finite coherence length. Issue 21 (30th November 2017) - Chaudhari, Mayank K.; Singh, Bipin K.; Pandey, Praveen C.
Abstract: Theoretical analysis of dye-sensitized solar cell integrated with photonic crystals based on coupled coherent and geometrical optics formalism has presented. The effect of structural parameters, such as thickness of layer, number of unit cells and light incident angle on the optical properties and photo-current magnification for the proposed photonic crystal based dye-sensitized solar cell have studied. The angular response of the cell in terms of light harvesting efficiency and cumulative photo-generation rate has also analysed. A strategy has presented to enhance the performance of the cell under oblique incidence. The effect of number of photonic crystal unit cells has also analysed in view of percentage enhancement in cumulative photo-generation rate. This work provides new insight into the design and tailoring of the photonic crystals to enhance the light harvesting efficiency in the solar cells.